TDP43 augments astrocyte inflammatory activity through mtDNA-cGAS-STING axis in NMOSD - Zhuhe Liu; Yunmeng Bai; Bingtian Xu; Haixia Wen; Kechun Chen; Jingfang Lin; Yuanyuan Wang; Jiangping Xu; Haitao Wang; Fudong Shi; Jigang Wang; Honghao Wang (Journal of Neuroinflammation)
Abstract Abnormality in transactivating response region DNA binding protein 43 (TDP43) is well-recognized as the pathological hallmark of neurodegenerative diseases. However, the role of TDP43 in neuromyelitis optica spectrum disorder (NMOSD) remains unknown. Here, our observations demonstrate an upregulation of TDP43 in both in vitro and in vivo models of NMOSD, as well as in biological samples from NMOSD patients. Single-nucleus RNA sequencing revealed that NMOSD induced A1-like reactive astrocytes and astrocyte mitochondrial dysfunction in mice. We further found that NMOSD provoked the translocation of TDP43 to mitochondria and the release of mitochondrial DNA (mtDNA) into the cytoplasm. NMOSD caused activation of mtDNA/cyclic GMP-AMP synthase (cGAS) / stimulator of interferon genes (STING) pathway and A1-type inflammatory activation in astrocytes. Crucially, the knockdown of TDP43 markedly ameliorated NMOSD-induced mitochondrial dysfunction and the activation of the cGAS/STING pathway in astrocytes. Conversely, overexpression of TDP43 exacerbated these pathological changes. Specific silencing astrocytic TDP43 ameliorated NMOSD-induced injury in mice, and conversely, TDP43 overexpression intensified the injury. Meanwhile, both cGAS and STING inhibitors attenuated NMOSD-induced injury in mice. In summary, our data suggest that TDP43 exacerbates inflammatory activation of astrocytes in NMOSD through upregulating the mtDNA/cGAS/STING signaling pathway. Therefore, targeting TDP43 represents a compelling therapeutic strategy for NMOSD.